1994
DOI: 10.3171/jns.1994.80.3.0527
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of antiprogesterones on human meningioma cells in vitro and in vivo

Abstract: The presence of the progesterone receptor (PR) in meningioma tissue has been confirmed by previous investigations. Studies have shown that the antiprogesterone drug, mifepristone, is a potent agent that inhibits the growth of cultured meningioma cells and reduces the size of meningiomas in experimental animal models and humans. However, these studies have not fully examined the relationship between the antitumor effects of an antiprogesterone agent and the expression of the PR. The present study examined the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 28 publications
1
28
1
4
Order By: Relevance
“…8 Despite evidence that antiprogesterone treatment reduces the size of meningioma, both in vitro and in vivo, such hormonotherapy is not part of the conservative management of meningioma. 9 Reports of spontaneous regression of meningiomas in the literature are rare. Apart from spontaneous resolution after intratumoral hemorrhage, 10 only 2 cases of regression have been reported in association with progestative hormonal treatment withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…8 Despite evidence that antiprogesterone treatment reduces the size of meningioma, both in vitro and in vivo, such hormonotherapy is not part of the conservative management of meningioma. 9 Reports of spontaneous regression of meningiomas in the literature are rare. Apart from spontaneous resolution after intratumoral hemorrhage, 10 only 2 cases of regression have been reported in association with progestative hormonal treatment withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…8) Administration of another antiprogesterone agent, onapristone, resulted in marked reduction of the meningioma size in both in vitro and in vivo studies. 16) However, no antiprogesterone therapies have been established yet for the treatment of meningiomas. 7) One study found that 63% of asymptomatic meningiomas did not exhibit tumor growth, and only 6% of all patients with lesions experienced symptoms during the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…29 İn vitro ve in vivo deneylerde mifepristone (RU486) ve onapristone uygulamasının tümör hücrelerinin gelişimini inhibe ettiği ve tümör hacminde azalma sağladığı gösterilmiştir. 30 Cerrahi olarak çıkarılamayan menenjiomlu hastalara uygulanan mifepristone tedavisi sonrası tümörde regresyon tespit edilmiştir. 31 Schwannomlar genellikle izole olarak ortaya çıkan tümörlerdir.…”
Section: Sonuçlarunclassified